Translating religious cultural element in Baqarah chapter into English: an analysis of the word 'Solah' - Ramli, Sulhah; A. Bakar, Arnida; Ahmad, Hisomudin; Abd. Rahman, Akmal Khuzairy (Universiti Sains Islam Malaysia, Persatuan Penterjemah Malaysia, Dewan Bahasa dan Pustaka, Institut Terjermahan dan Buku Malaysia, 2019)
The paper attempts to analyze the meaning of 'solah' that has specific meanings in the Holy Quran. COmponential analysis is used to identify the intended degree of meanings of the word. The study concluded that the word 'solah' used in the English translation does not carry the same intended meaning as it is in Arabic.